Broadcasting services: A Study of the Development of Thai Communications Laws in the 20th Century - Pasuna, Chaiwat (Journal of Digital Communications, 2021)
This article studies the development of Thai communications laws in the 20th century. The objectives of this study were: The changing of broadcasting services in Thai society, and the dynamics of communication laws that study through a historical perspective. The concept of the article is social dynamics and social changing. The article carried out a series of primary and secondary sources along with historical research. The results of the study show that the development of communications law in the 20th century, which has changed according to the context of Thai society in 3 periods: During the Thesaphiban countries administrative management, During the regime change and World War II, and During the Cold War. In addition, the law is dynamic, which arises from the conditions of the availability of social communications technology. Laws have evolved according to more diverse roles. It affects the formulation of government laws to cover such as licensing and penalties. This study brings to the understanding of the changing of law and the development of telecommunication technology which occurred in Thailand throughout the 20th century.